Maximizing Energy Efficiency and Minimizing Environmental Emissions in the Process Industri Using Thermal Pinch Analysis - Zainuddin A. Manan (ASEAN Journal of Chemical Engineering, 2004)
Efforts to increase plant energy efficiency intensify with the continuing increase in fuel prices and the growing global concern for environmental emis~ions. As new processes and technologies emerge, existing procedures are pressured to increase efficiency and maintain profitability to remain competitive. Many installations have focused on energy efficiency upgrading to increase profitability. Energy efficiency measures employed in local industries, however, have been generally confined to good housekeeping techniques and the upgrade of utility systems, such as boilers, steam systems, chillers, hot oil circuit, and refrigeration and cooling systems. Very few companies are willing venture into process operations to further reduce their energy consumption. As a result, the benefits that can be derived from retrofit projects have been greatly limited. The advent of thermal pinch analysis provid~5 a comprehensive and systematic approach to maximize plant energy efficiency. This paper highlights some key features of thermal pinch analysis aimed at maximizing energy efficiency and reducing environmental emissions. It begins by describing the significance of pinch design targets and the use of simple graphical tools as guides for process modifications to reduce further energy usage and emissions. Finally, the paper highlights how the interactions between process plant and utility systems can be exploited to a company's advantage.